2007
DOI: 10.1007/s10562-007-9052-6
|View full text |Cite
|
Sign up to set email alerts
|

Modified versions of sulfated zirconia as catalysts for the conversion of xylose to furfural

Abstract: Conventional (per)sulfated bulk zirconia, mesoporous sulfated zirconia and (per)sulfated zirconia supported on an ordered mesoporous silica, with or without aluminium incorporation, were examined as acid catalysts for the dehydrocyclisation of xylose into furfural. Furfural yields of up to 50% could be achieved at >90% conversion with the modified zirconia catalysts, which is better than that achievable with H 2 SO 4 (using approximately the same equivalent amount of sulfur.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(76 citation statements)
references
References 52 publications
3
70
0
1
Order By: Relevance
“…Traditional operation conditions include temperature in the 200-250 °C range and the presence of sulfuric acid as catalyst, but alternative acids have been proposed, such as formic acid [195]. However, efforts to improve the process by heterogeneous catalysis have been carried out [196][197][198][199] and the recent employment of ionic liquids as catalysts has opened a new opportunity to furfural production [200,201]. Although furfural can be the starting block for the synthesis of a series of furan derivatives with high commercial interest [87,202], 5-hydroxymethylfurfural (HMF) is an even more attractive platform [203].…”
Section: Chemicals From Hemicellulosementioning
confidence: 99%
“…Traditional operation conditions include temperature in the 200-250 °C range and the presence of sulfuric acid as catalyst, but alternative acids have been proposed, such as formic acid [195]. However, efforts to improve the process by heterogeneous catalysis have been carried out [196][197][198][199] and the recent employment of ionic liquids as catalysts has opened a new opportunity to furfural production [200,201]. Although furfural can be the starting block for the synthesis of a series of furan derivatives with high commercial interest [87,202], 5-hydroxymethylfurfural (HMF) is an even more attractive platform [203].…”
Section: Chemicals From Hemicellulosementioning
confidence: 99%
“…[8][9][10][11]13,14,16,17,19,47,48 The TiO 2 /CB catalyst allows reaching relatively high Fur yields in short reaction times (e.g. in comparison to H 2 Ti 3 O 7 nanosheets).…”
Section: Xylose Dehydration To Furfuralmentioning
confidence: 99%
“…4 The replacement of the homogeneous catalysts by stable, recyclable, active and selective solid catalysts would also have economic and environmental benefits on the large-scale production of furfural, by minimizing corrosion problems and amounts of neutralization waste, and facilitating the recovery and reutilization of the catalyst. For this reason, several solid acid catalysts have been tested in the dehydration of xylose into furfural, including zeolites, 8,10,11,13 sulfated metal oxides, [14][15][16] organic polymers, 17,18 supported heteropolyacids, 19 or exfoliated metal oxide nanosheets. 20 While some very promising results have been obtained, these studies also point out how challenging it remains to find catalysts with high activity and selectivity, that are structurally and chemically stable during repeated utilizations and stable towards coke formation.…”
Section: Introductionmentioning
confidence: 99%
“…grafting of the ionic liquid is the disappearance of the peak corresponding to surface Si-OH groups of the silica support after immobilization. NMR signals centred at -91 and -101 ppm, assigned to (SiO) 2 Si(OH) 2 and (SiO) 3 Si-OH groups, respectively, are strongly diminished, indicating extensive grafting of the IL at the silica surface. A very small peak at -101 ppm and the small shoulder at -100 ppm assigned to (SiO) 3 Si-OH are observed along with the broadening of the peak at -111 ppm assigned to (SiO) 4 Si groups, indicating the presence of residual silanol groups.…”
Section: Synthesis and Surface Modification Of Nanosilica Catalystsmentioning
confidence: 99%
“…NMR signals centred at -91 and -101 ppm, assigned to (SiO) 2 Si(OH) 2 and (SiO) 3 Si-OH groups, respectively, are strongly diminished, indicating extensive grafting of the IL at the silica surface. A very small peak at -101 ppm and the small shoulder at -100 ppm assigned to (SiO) 3 Si-OH are observed along with the broadening of the peak at -111 ppm assigned to (SiO) 4 Si groups, indicating the presence of residual silanol groups. Similar observations have been reported by Hölderich et al 24 Additionally, the two peaks observed at -59 ppm and -67 ppm (Si-3-IL-HSO 4 sample) assigned to Si-O-SiR-(OEt) 2 and (Si-O) 2 -SiR-OEt, respectively, 24 further confirm the ionic liquid attachment at the silica surface from organic cation moiety either via one or two Si-O-Si covalent bonds (Scheme 2).…”
Section: Synthesis and Surface Modification Of Nanosilica Catalystsmentioning
confidence: 99%